Alternative patch repair materials for rebar corrosion damage - Jassa, Primesh (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2017)
Reinforced concrete (RC) is extensively used in the construction industry. It is particularly used to guarantee that infrastructure assets around the world last for multiple years whilst ensuring that the structural integrity and serviceability of the structure is maintained. However, in practice countless RC constructions are failing prematurely due to a large number of factors of which the corrosion of steel embedded within concrete is the most significant (Matthews et al., 2003). Steel corrosion is particularly pernicious to concrete due to the expansive nature of the corrosion by-products formed, which commonly leads to cracking and spalling. One of the most common methods adopted in the rehabilitation of corrosion damaged concrete is the patch repair procedure. However, in practice this method has shown to often be unreliable as a consequence of the widespread occurrence of shrinkage cracking and poor substrate-patch adhesion leading to debonding of the patch repair. From a practical point of view, such failed repair systems essentially restore the repaired concrete back to a deteriorated state. The underlying cause of poor durability in patch repairs is attributed to a range of reasons including, the lack of understanding of the substrate-patch composite system and the limited availability of appropriate design standards. Furthermore, there is a lack of understanding in the repair industry on the critical material properties actually required for durable patch repairs. There is a common belief that repairing concrete with specialised proprietary repair materials would guarantee durability. However the widespread premature failure of patch repairs conducted using such materials has proven the contrary. A proper patch repair process includes treatment of the corroded steel, adequate substrate surface preparation, installing sacrificial anodes (at least for chloride contaminated concrete) and surface coating. In principle, if this process is correctly followed then the material requirements for a durable, non-structural repair would be to fill in the cavity created by removing contaminated concrete, resist shrinkage induced cracking and/or debonding and provide protection against chloride ingress (in chloride environments). The material used for patch repairs could be any appropriate repair material and it does not specifically need to be a specialised cementitious repair mortar. This dissertation presents an understanding of the materials and issues concerning the durability and serviceability of patch repairs, with the aim of identifying alternative non-structural patch repair materials for the durable repair of corrosion-damaged concrete structures. The potential patch repair materials studied in this dissertation were rubberised waterproofing bitumen, polymer (copolymer of vinyl acetate and ethylene) with 5% cement replacement and 60%, 80% and 100% fly ash (FA) mortar. Patch repairs were conducted on substrate moulds to test application and observe cracking/debonding occurrence. Furthermore, compressive strength, durability index, accelerated drying shrinkage, restrained shrinkage, workability and SEM tests were conducted. It was concluded that the 60% FA repair material had the best overall performance with the polymer-cement concrete exhibiting good bonding and crack resistance properties. This research established that innovative alternative repair materials such as a 60% FA or polymer-cement concrete material, can be developed for non-structural patch repairs with improved long-term performance relative to conventional materials. The research has further provided a foundation for the development and design of durable repair mortars by identifying the principal material performance properties required of such materials.